Brain MR patterns in inherited disorders of monoamine neurotransmitters: an analysis of 70 patients - Kuseyri Hübschmann, Oya; Mohr, Alexander; Friedman, Jennifer; Manti, Filippo; Horvath, Gabriella; Cortès-Saladelafont, Elisenda; Mercimek-Andrews, Saadet; Yildiz, Yilmaz; Pons, Roser; Kulhánek, Jan; Oppebøen, Mari; Koht, Jeanette Aimee; et al. (Journal of inherited metabolic disease, 2021)
Inherited monoamine neurotransmitter disorders (iMNDs) are rare disorders with clinical manifestations ranging from mild infantile hypotonia, movement disorders to early infantile severe encephalopathy. Neuroimaging has been reported as non-specific. We systematically analyzed brain MRIs in order to characterize and better understand neuroimaging changes and to re-evaluate the diagnostic role of brain MRI in iMNDs. 81 MRIs of 70 patients (0.1-52.9 years, 39 patients with tetrahydrobiopterin deficiencies, 31 with primary disorders of monoamine metabolism) were retrospectively analyzed and clinical records reviewed. 33/70 patients had MRI changes, most commonly atrophy (n = 24). Eight patients, six with dihydropteridine reductase deficiency (DHPR), had a common pattern of bilateral parieto-occipital and to a lesser extent frontal and/or cerebellar changes in arterial watershed zones. Two patients imaged after acute severe encephalopathy had signs of profound hypoxic-ischemic injury and a combination of deep gray matter and watershed injury (aromatic l-amino acid decarboxylase (AADCD), tyrosine hydroxylase deficiency (THD)). Four patients had myelination delay (AADCD; THD); two had changes characteristic of post-infantile onset neuronal disease (AADCD, monoamine oxidase A deficiency), and nine T2-hyperintensity of central tegmental tracts. iMNDs are associated with MRI patterns consistent with chronic effects of a neuronal disorder and signs of repetitive injury to cerebral and cerebellar watershed areas, in particular in DHPRD. These will be helpful in the (neuroradiological) differential diagnosis of children with unknown disorders and monitoring of iMNDs. We hypothesize that deficiency of catecholamines and/or tetrahydrobiopterin increase the incidence of and the CNS susceptibility to vascular dysfunction.
Online veröffentlicht: 14. Januar 2021
Gesehen am 09.08.2023